Anti-inflammatory and Antioxidant Properties of Finger Millet (Eleusine coracana (L.) Gaertn.) Varieties Cultivated in Sri Lanka. (1st October 2021) - Jayawardana, Sooriya Arachchige Sachini; Samarasekera, Jayanetti Koralalage Ramani Radhika; Hettiarachchi, Gardhi Hettiarachchige Chamari Madhu; Gooneratne, Jaanaki; Choudhary, Muhammad Iqbal; Jabeen, Almas
Abstract : The prevalence of inflammatory-mediated and oxidative stress-associated diseases is increasing worldwide, creating an increasing demand for novel sources of anti-inflammatory agents and antioxidants. This study was focused on determining the in vitro arachidonate 5-lipoxygenase (A5-LOX), xanthine oxidase (XO), hyaluronidase and oxidative burst inhibitory activities, and antioxidant properties of Ravi, Rawana, and Oshadha finger millet varieties using ethanolic and methanolic extracts. Among all extracts, the methanolic extract of Oshadha exhibited the highest A5-LOX (IC50 value: 484.42  μ g/ml) and XO (IC50 value: 764.34  μ g/ml) inhibitory activities. All extracts showed less than 50% hyaluronidase inhibitory activity at 1 mg/ml concentration. Methanolic extracts showed moderate inhibitory potential on reactive oxygen species (ROS) generated from whole blood phagocytes, with IC50 values ranging between 26.9 and 27.7  μ g/ml, when compared to ibuprofen (IC50 value: 11.18  μ g/ml). All extracts showed potent inhibition of ROS produced from polymorphonuclear neutrophils isolated from human blood when compared to ibuprofen (IC50 value: 2.47  μ g/ml) and IC50 values of methanolic and ethanolic extracts ranged from 0.29 to 0.47  μ g/ml and 1.35 to 1.70  μ g/ml, respectively. All extracts had significantly high amounts of phenolic compounds including flavonoids and the potential to scavenge 2, 2 ′ -azino-bis (3-ethylbenzothiazoline-6-sulfonic) acid (ABTS) cation, 2, 2-diphenyl-1-picryl-hydrazyl (DPPH), and oxygen radicals. Besides, they were able to reduce metal ions and chelate metal ions terminating radical generating reactions. This is the first report of A5-LOX, XO, hyaluronidase, and oxidative burst inhibitory properties of any extract of any finger millet variety cultivated in Sri Lanka. The findings revealed the potential of using these finger millet extracts as natural sources of anti-inflammatory drug candidates. Additionally, the findings indicated that Ravi, Rawana, and Oshadha varieties are good sources of antioxidants. Therefore, consumption of these finger millet varieties on a regular basis may play an important role in the prevention and dietary management of oxidative stress-associated diseases.